The changing life course - Hutchison, Elizabeth D (Thousand Oaks, Calif., 1999)
Includes bibliographical references (p. 295-319) and index.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Human behavior; Social structure; Social service; Psychology, Social.; Psychologie sociale; Comportement humain; Hành vi của con người; Văn hóa xã hội; Dịch vụ xã hội